THE PARADOXICAL POLICIES, POLITICS OF TASTES, AND CLASSIC INDONESIAN EXPLOITATION CINEMA OF THE NEW ORDER REGIME - Imanjaya, Ekky (JWP (Jurnal Wacana Politik), 2024)
Although the New Order Regime (1966-1998) was widely known for its strict censorship and government control, there was a simultaneous rise in producing exploitation films with graphic and provocative images. This kind of cinema was exported internationally in the 1980s and re-released in the 2000s by transnational DVD distributors. This article analyzed the transformation of exploitation films, which were disregarded and undervalued by the Government, cultural elites, and cinema critics. It explored how these films became a battleground for the politics of taste and resulted in a series of contradictions within the political policies of the New Order. The study focused on policy studies, examining film-related policies (such as presidential decree and censorship regulations), and analyzed the findings by thoroughly examining the regulations’ trends, patterns, and anomalies. As a result, paradoxically, the New Order had to undertake trial and error towards the films that they were actually shunned, which resulted in the blooming of this kind of movie.